Poetic Plagiarism in the Book of Al-Juman in the Simulations of Al- Qur’an - Azab Abdullah , Researcher. Suad; Abdul-Nabi Ali , Prof. Dr. Murtada (Basra studies journal, 2023)
The researchers found that there were authorized and hidden thefts but referred to them in terms of theft indirectly.so, the researchers divided the research on this basis with clarification and explaining of Ibn Naqia’s speech and sometimes his critical ideas.